2022
DOI: 10.3390/s22124384
|View full text |Cite
|
Sign up to set email alerts
|

Mechanocardiography in the Detection of Acute ST Elevation Myocardial Infarction: The MECHANO-STEMI Study

Abstract: Novel means to minimize treatment delays in patients with ST elevation myocardial infarction (STEMI) are needed. Using an accelerometer and gyroscope on the chest yield mechanocardiographic (MCG) data. We investigated whether STEMI causes changes in MCG signals which could help to detect STEMI. The study group consisted of 41 STEMI patients and 49 control patients referred for elective coronary angiography and having normal left ventricular function and no valvular heart disease or arrhythmia. MCG signals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…Earlier studies have shown that MCG can detect a wide range of abnormalities in cardiac function caused by myocardial infarction and heart failure (Inan et al 2018, Hossein et al 2019, Mehrang et al 2020, Blomster et al 2021, Morra et al 2021b. In the literature, a supervised machine learning approach was used, and and it is shown that -in line with the present findingsthe strength features in systolic windows were lower in patients with ST elevation myocardial infarction than in control subjects having normal left ventricular function (Koivisto et al 2022b). The clinical precision of these methods for the diagnosis of myocardial infarction or heart failure is, however, limited; inter-individual variation in all signal features is large, resulting in significant overlap between the patient groups and healthy controls, causing a high risk of misclassification for an individual subject.…”
Section: Discussionsupporting
confidence: 83%
“…Earlier studies have shown that MCG can detect a wide range of abnormalities in cardiac function caused by myocardial infarction and heart failure (Inan et al 2018, Hossein et al 2019, Mehrang et al 2020, Blomster et al 2021, Morra et al 2021b. In the literature, a supervised machine learning approach was used, and and it is shown that -in line with the present findingsthe strength features in systolic windows were lower in patients with ST elevation myocardial infarction than in control subjects having normal left ventricular function (Koivisto et al 2022b). The clinical precision of these methods for the diagnosis of myocardial infarction or heart failure is, however, limited; inter-individual variation in all signal features is large, resulting in significant overlap between the patient groups and healthy controls, causing a high risk of misclassification for an individual subject.…”
Section: Discussionsupporting
confidence: 83%
“…In this context, various sensors such as ECG, accelerometer, and other sensors were used. For example, in [ 53 , 73 , 104 , 117 , 125 ], the ECG sensors ADAS1001, Shimmer 3, BMD101, ADXL355, and ADS1291 were used in combination with other materials to build a wearable device that collects records used to detect or predict cardiovascular disease. In contrast, the authors in [ 114 ] used the DS18B20 temperature sensor and ADXL1335 accelerometer to develop the desired wearable system.…”
Section: Resultsmentioning
confidence: 99%
“…Motion artifacts were removed from the signals (SCG, GCG, and ECG) using an automated algorithm. The algorithm was originally developed for a more challenging usage scenario of removing motion artifacts from chest pain (myocardial infarction, STEMI) recordings [30]. It was straightforward to deploy same approach for this study.…”
Section: Motion Artifact Removalmentioning
confidence: 99%
“…Feature extraction was next performed with features that we previously developed in another study: (1) signal strength, (2) amplitudes and time-intervals (e.g., R-peak to AO and AC), and (3) stability within specific signal windows defined using the R-peaks of ECG (e.g., around different heart sounds, S1-S3) [30]. These features-i.e., their Matlab R2017a implementations-had been developed beforehand, so we did not develop new features based on the data we already had.…”
Section: Feature Extractionmentioning
confidence: 99%